Enhanced Faraday rotation in proximitized monolayer transition metal dichalcogenides. (25th August 2020) - Dai, Hongwei; Song, Qi; Da, Haixia
Abstract: Monolayer transition metal dichalcogenides (TMDCs) under the application of a magnetic exchange field carry the nontrivial optical Hall conductivity and thus exhibit the nonzero Faraday rotation (FR) angle. However, the tradeoff between the FR angle and transmission hinders their possible applications in magnetic-optical (MO) devices. Here, we theoretically show that a heterostructure of two photonic crystals with proximitized monolayer TMDCs enables the enhancement of the FR angle and transmission simultaneously through the combination of a four-band Hamiltonian model, Kubo formula and transfer matrix method. The MO improvement in the hybrid structure in both the FR angle and transmission is determined by the combined effects from the localized electromagnetic field at the interface between the two photonic crystals and the satisfaction of the phase match condition. Our work opens up an alternative opportunity to use TMDCs in two-dimensional MO fields in the visible frequency range.